1994
DOI: 10.1111/j.1365-2230.1994.tb02705.x
|View full text |Cite
|
Sign up to set email alerts
|

Dorfman-Chanarin syndrome (neutral lipid storage disease). A case report

Abstract: We describe the case of a woman from a small town in the south of Spain, with consanguineous parents, who presented with the complete syndrome. The main clinicopathological characteristics are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Considering that the most important site for the pathogenesis of corni-¢cation disorders is not the basal layer but the upper spinous and the granular layers of the epidermis, we hypothesized that lipid vacuoles in the basal cells are not important in the pathogenesis of ichthyosis in DCS with CGI-58 mutations. In all previous reports, DCS patients showed ichthyosis, but the lipid vacuoles in the basal epidermal layer were not always seen (Dorfman et al, 1974;Chanarin et al, 1975;Miranda et al, 1979;Elias and Williams, 1985;Srebrnik et al, 1987;Venencie et al, 1988;Williams et al, 1988;Banuls et al, 1994;Kaassis et al, 1998;Wollenberg et al, 2000;Pena-Penabad et al, 2001). Srebrnik et al (1998) suggested that large lipid vacuoles were not correlated with DCS clinical severity.…”
Section: Discussionmentioning
confidence: 91%
“…Considering that the most important site for the pathogenesis of corni-¢cation disorders is not the basal layer but the upper spinous and the granular layers of the epidermis, we hypothesized that lipid vacuoles in the basal cells are not important in the pathogenesis of ichthyosis in DCS with CGI-58 mutations. In all previous reports, DCS patients showed ichthyosis, but the lipid vacuoles in the basal epidermal layer were not always seen (Dorfman et al, 1974;Chanarin et al, 1975;Miranda et al, 1979;Elias and Williams, 1985;Srebrnik et al, 1987;Venencie et al, 1988;Williams et al, 1988;Banuls et al, 1994;Kaassis et al, 1998;Wollenberg et al, 2000;Pena-Penabad et al, 2001). Srebrnik et al (1998) suggested that large lipid vacuoles were not correlated with DCS clinical severity.…”
Section: Discussionmentioning
confidence: 91%
“…Alopecia was a rare finding (only two cases), being described as patches of cicatricial alopecia; 8,12 total alopecia of the scalp was observed in our patient. Nails were normal in most cases, but thickening, 8,9 pitting and longitudinal striations, 8 yellow‐black discoloration, 9 pitting and onychoschizia 13 have been described. Transverse leuconychia, noticed in our patient, has not previously been reported.…”
Section: Clinical Features In Dorfman–chanarin Syndromementioning
confidence: 99%
“…This syndrome is associated with multiple organ involvement. Other clinical findings aside from ichthyosis include hepatomegaly, bilateral ectropion, cataract, muscle weakness, bilateral sensorineural deafness, splenomegaly, short stature, small ears, strabismus and mental retardation 64–74 . In addition, clinical findings, such as microcephaly, cardiomyopathy, nystagmus, eclabion, rickets, renal eccrine gland and pancreatic involvement, are also observed in rare cases 75–80 .…”
Section: Discussionmentioning
confidence: 99%
“…Other clinical findings aside from ichthyosis include hepatomegaly, bilateral ectropion, cataract, muscle weakness, bilateral sensorineural deafness, splenomegaly, short stature, small ears, strabismus and mental retardation. [64][65][66][67][68][69][70][71][72][73][74] In addition, clinical findings, such as microcephaly, cardiomyopathy, nystagmus, eclabion, rickets, renal eccrine gland and pancreatic involvement, are also observed in rare cases. [75][76][77][78][79][80] The most common clinical findings in patients were ichtyosis 100% and hepatomegaly 60%, and the others were bilateral ectropion, cataract, neurosensory deafness and splenomegaly (29%, 22%, 17% and 13% respectively).…”
Section: Liver Disease Liver Phenotype Genotype/mutationmentioning
confidence: 99%